When past and new experiences meet. Negotiating meaning with 3-D materials in early childhood education - Fredriksen, Biljana C. (FormAkademisk, 2011)
This article suggests that the process of meaning making is closely related to embodied experience and social interaction. The article is based on a study of specific contexts of visual arts education with 3–5 year old children. The study aims to enlarge understanding of relationships between children’s experience with three-dimensional (3-D) materials and their meaning-making processes. Empirical data were collected through observations of children’s play and video documentation of interactions between a practitioner-researcher and pairs of children. The data were analysed through interpretative, contextual, arts-based inquiry, and the findings were presented in the form of vignettes. Two vignettes with 3-year-old boys are presented in this article, in order to discuss how the boys’ explorative play with 3-D materials formed the basis for their experience, problem solving, imaginative response, multimodal expressions and meaning making. It is further suggested that the children’s new understandings emerge from the ‘meetings’ between their past and new experiences, stimulated by the 3-D material’s affordances and resistance.